Acanthamoeba keratitis: a challenge in diagnosis and the role of amniotic membrane transplant as an alternative therapy (Medical Journal of Indonesia, 2018)
Acanthamoeba keratitis (AK) is a very rare, sight-threatening corneal disease caused by the infection of a free-living amoeba. The aim of this report was to demonstrate the challenges in the diagnosis of AK with an atypical presentation. Amniotic membrane transplantation (AMT) was done in this case to accelerate wound healing. A woman who frequently used contact lens came with redness and a whitish spot in her left eye 2 weeks before admission. There was a history of rinsing contact lens in tap water. The patient had already been on a topical steroid for 2 weeks. Visual acuity of the left eye was light perception with wrong projection. Examination of the left cornea showed a semi-circular central ulcer with a 5.8-mm area and 1/3 stromal depth. It is surrounded by a feathery-edge infiltrate with positive satellite lesions but without hypopyon. It was diagnosed as corneal ulcers due to mixed infection (bacteria and fungi). After 2 weeks of bacterial and fungal therapy, the size of the ulcer decreased, but the corneal infiltrate remained; therefore, an Acanthamoeba culture was done to determine the possibility of Acanthamoeba infection. Two weeks after the Acanthamoeba topical therapy, the visual acuity improved. AMT was performed to accelerate wound healing. Two months post-AMT, visual acuity improved to 1/60 with no conjunctival or ciliary vasodilation, and the ulcer was resolved. The patient was planned to undergo keratoplasty. The diagnosis of AK with an atypical presentation is challenging. AMT can be used as an alternative therapy to accelerate wound healing.